A Review on Mechanisms involved in TRPM3 Channel and Mitochondrial Modulation with Mefenamic Acid-Dicyclomine Combination: Review Article (Journal of Pharma Insights and Research, 2025)
Recent literature on molecular and cellular investigations have unveiled novel mechanisms underlying the therapeutic effects of mefenamic acid-dicyclomine combination (MAC). Proteomics have identified previously unknown interactions with Transient Receptor Potential Melastatin 3 (TRPM3) channels, suggesting a crucial role in pain modulation beyond conventional prostaglandin inhibition. Emerging evidence indicates MAC's involvement in mitochondrial dynamics and cellular stress responses, particularly in uterine smooth muscle cells. High-throughput screening has also shown potential interactions with calcium-activated potassium channels (BK channels), contributing to its antispasmodic effects. The main findings include MAC's influence on microglial activation and neuroinflammatory pathways in visceral pain processing. Recent pharmacovigilance data has identified rare but significant adverse effects, including drug-induced liver injury patterns and autonomic dysregulation in susceptible populations. Metabolomic studies have shown novel metabolic pathways affected by long-term MAC usage, particularly involving sphingolipid metabolism and cellular energy homeostasis. This information combined with reported adverse events, necessitate careful consideration in specific patient populations, especially those with pre-existing mitochondrial disorders or ion channelopathies